Combined whole-body dynamic and static PET/CT with low-dose [18F]PSMA-1007 in prostate cancer patients - Sachpekidis, Christos; Pan, Leyun; Grözinger, Martin; Strauss, Dimitrios; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2024)
In addition to significant improvements in sensitivity and image quality, the recent introduction of long axial field-of-view (LAFOV) PET/CT scanners has enabled dynamic whole-body imaging for the first time. We aim herein to determine an appropriate acquisition time range for static low-dose [18F]PSMA-1007 PET imaging and to investigate the whole-body pharmacokinetics of [18F]PSMA-1007 by dynamic PET with the LAFOV Biograph Vision Quadra PET/CT in a group of prostate cancer patients.